Mechanical Test on Aluminum Alloy with Maximal Soluble SiC Reinforcement - G. Pruthviraju; Sunil G. Dambhare; Bhargav Prajwal Pathri; M. Ramakrishna; L. Gokulanathan; K. Balamurugan; W. Shumet (Advances in Materials Science and Engineering)
This work deals with the characteristics of LM-13alloy under cyclic stress with and without 63% by weight of SiC-reinforced composite particle reinforcements both cast and tempered at ambient condition. The hardness of the composite sample before and after tempering was 112 HV and 134HV. The tempered sample shows 16.4% increment. UTS of base alloy and the composite was determined to be 165 MPa and 149 and 210, and 145 and 192, respectively. The UTS decreases by 12% in cast state and 8% in tempered condition. The tempered base alloy shows an increment of 21%, and the 0.25% proof stress increased by 28%. After heat treatment, the elongation at the break of the base alloy improved to 3.5%. The tempered specimen shows an increased fatigue performance of approximately 43%. The fatigue life was determined to be about 165 repetitions at the 75 MPa level of stress with 75% of UTS utilization. Decohesion of a silicon particulate interaction and in certain circumstances, the subsequent breakdown of SiC particles has led to fractures in composites. The preheated eutectic silicon that had an almost gain round shape will withstand crack growth development, as the aluminum matrix had a higher cohesive force compared to reinforced SiC particles which provide less strain increase locations. Stronger bonds among silica eutectic and aluminum matrices produced the fracture across their contact, silicon breaks owing to the application of the fatigue load and lead to specimen failure.